Short communication: A comparison of the rate of polyethylene decomposition among Bacillus spp., Pseudomonas spp., and Escherichia coli bacteria - MICHAEL PHILANDER; PAULETTE RAGOBEER; RUTH DANIEL (Smujo International, 2019)
Abstract. Philander M, Ragobeer P, Daniel R. 2019. Short communication: A comparison of the rate of polyethylene decomposition among Bacillus spp., Pseudomonas spp., and Escherichia coli bacteria. Nusantara Bioscience 11: 97-100. This study did a comparative analysis of the rate of polythene plastic decomposition among three species of bacteria namely, Bacillus spp., Pseudomonas spp., and Escherichia coli. The three bacterial species were cultured and grown in 2-liter polyethylene terephthalate bottles with nutrient broth separately in triplicates along with a control that did not include any bacteria. These bottles were left undisturbed at room temperature for three months (92 days) after which the containers were subjected to sterilization. Plastic weights were taken using an electronic scale and compared with original values. From the results, it showed that in the three months there was a relatively large amount of degradation that occurred. Bacillus spp. and E.coli bacteria yielded similar results and moved at a rate faster than the Pseudomonas spp., A daily rate for each bacterial species was calculated and a predictive figure based on rates was made. If the rates remained constant there would be total degradation of the polyethylene plastics by the Bacillus spp., E. coli and Pseudomonas spp., in 11.45, 11.45 and 12.35 years respectively. This is a significant finding since in nature plastics can take hundreds of years to decompose.